Design and application of path-based health education form for inpatients in rheumatology and immunology department (风湿免疫科住院患者健康教育路径表单的设计与应用) - ZHONG Yingying (仲莹莹); XU Renju (徐任菊); ZHU Yuxuan (朱昱璇); ZHANG Qiong (张琼) (中西医结合护理)
Objective To explore the design and application effect of path-based health education form for inpatients in the Department of Rheumatology and Immunology. Methods A health education group in the Department of Rheumatology and Immunology was established. By reviewing literature, consulting experts, oriented by patient needs, and combining clinical pathways, a path-based health education form for inpatients was formulated. Homogeneous training and examination were conducted to nurses. Totally 1 047 patients admitted to hospital from September 2021 to February 2022 were selected, and the patients' health knowledge, patient satisfaction and nurses' satisfaction with application of path-based health education form were measured. Results After the path-based health education form was used, the implementation rate of various health education including admission guidance, dietary guidance, activities, medication guidance and discharge guidance reached 100. 00% during the patient's stay in the hospital, and the satisfaction of patients and nurses was significantly improved (P＜0. 01). The mastery rate of diet knowledge, activities, disease and medication knowledge were increased significantly after implementation of path-based health education form (P＜0. 01). Conclusion The application of the path-based health education form in inpatients could improve the effect of health education, enhance the nursing quality, and increase working efficiency. (目的 探讨风湿免疫科住院患者健康教育路径表单的设计及应用效果。方法 成立风湿免疫科健康教育小组, 通过查阅文献、咨询专家、以患者需求为导向、结合临床路径制定风湿免疫科住院患者健康教育路径表单, 对责任护士进行同质化培训与考核。于2021年9月—2022年2月选择1 047名住院患者进行干预, 评价患者健康知识掌握程度、患者满意度及护士使用满意度。结果 共回收1 028份健康教育路径表单。健康教育路径表单运用后, 患者在院期间各项健康教育落实率如入院指导、饮食指导、活动与休息、用药指导及出院指导达100. 00%, 患者饮食、休息与活动、疾病与用药知识掌握率、较入院时均有提高, 差异有统计学意义(P＜0. 01)。患者满意度与护士使用满意度高于表单运用前(P＜0. 01)。结论 健康教育路径表单在风湿免疫科住院患者中的应用, 有助于提高患者健康教育干预效果, 有效提升护理工作质量, 提高护理人员工作效率。)